Interleukin‐6 deletion in mice driven by aP2‐Cre‐ERT2 prevents against high‐fat diet‐induced gain weight and adiposity in female mice. (1st July 2014) - Navia, B.; Ferrer, B.; Giralt, M.; Comes, G.; Carrasco, J.; Molinero, A.; Quintana, A.; Leclerc, J.; Viollet, B.; Señarís, R. M.; Hidalgo, J.
Abstract Aim Interleukin‐6 (IL‐6) is a major cytokine controlling body weight and metabolism, but because many types of cells can synthesize and respond to IL‐6 considerable uncertainty still exists about the mechanisms underlying IL‐6 effects. Therefore, the aim of this study was to analyse the effects of tissue‐specific deletion of IL‐6 using a fatty acid binding protein (aP2) promoter‐Cre inducible system (aP2‐Cre‐ERT2). Methods Tissue‐specific IL‐6 KO mice (aP2‐IL‐6 KO mice) were produced upon tamoxifen administration and were fed a high‐fat diet (HFD, 58.4% kcal from fat) or a control diet (18%) for 14 weeks. Results aP2‐IL‐6 KO female mice on a HFD gained less weight and adiposity than littermate wild‐type mice, but these effects were not observed in males. Hypothalamic factors such as NPY and AgRP showed a pattern of expression consistent with this sex‐specific phenotype. PGC‐1α expression was increased in several tissues in aP2‐IL‐6 KO female mice, which is compatible with increased energy expenditure. Serum leptin, insulin, glucose, cholesterol and triglycerides levels were increased by HFD, and in females IL‐6 deficiency reversed this effect in the case of insulin and cholesterol. HFD induced impaired responses to insulin and glucose tolerance tests, but no significant differences between genotypes were observed. Conclusion The present results demonstrate that deletion of IL‐6 driven by aP2‐Cre regulates body weight, body fat and metabolism in a sex‐specific fashion.